Tradisi Ziarah dan Korelasinya dengan Peringatan Hari Raya Sukkoth ditinjau dari Nehemia 8:1-19 - Susanto, Hery; Caesar Susetyo Adi, Eben Haezer (SAGACITY : Journal of Theology and Christian Education, 2024)
Pilgrimage as an important part of every religious service is important in realizing one's faith. The Israelites longed to be able to reflect their faith through the holiday of Sukkoth or the Feast of Tabernacles after hundreds of years of forgetting it because of the conditions and situation of the exile they experienced. Facts on the ground show that until now humans often carry out pilgrimage practices to places that are considered sacred and contain historical aspects. How effective and how to interpret the pilgrimage from the human spiritual dimension to present God in the reality of everyday life.